Szacowanie przepływów pieniężnych i stopy dyskontowej w dochodowym podejściu do wyceny przedsiębiorstwa - Nita, Bartłomiej (Cash Flow and Discount Rate Estimation Under the Discounted Cash Flow Valuation Method, 2008)
The paper describes in details four methods for valuing companies under the discounted cash flow valuation approach: - free cash flow valuation, - equity cash flow valuation, - capital cash flow valuation, - adjusted present value. In the paper, the ways of estimating cash flows for each method were depicted. The author explains how to choose the appropriate discount rate for the methods described in the article. The paper focuses on the free cash flow valuation method because it is the most widely used in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 122-137